Targeting QKI-7 in vivo restores endothelial cell function in diabetes - Chunbo Yang (Nature Portfolio, 2020)
Vascular endothelial cell (EC) dysfunction contributes to the occurrence of diabetic complications. Here the authors report that in diabetic conditions, upregulation of the RNA binding protein QKI-7 in ECs due to the imbalance of RNA splicing factors CUG-BP and hnRNPM contributes to EC dysfunction, and that in vivo QKI-7 silencing improves blood flow recovery in diabetic mice with limb ischemia.